KELUARGA SAKINAH: IDEALISME DAN IMPLEMENTASI DALAM AL-QUR’AN - Salsabila, Siti Nurul; Sarlina, Sarlina; Aminah, Nurul; Nudya, Yusi; Shifa, Naina; Chandra, Andi; Ahmad, Ilham; Gozali, Imron (Al-Usroh : Jurnal Hukum Keluarga Islam, 2024)
The Koran, as the holy book of Muslims, not only contains spiritual guidance but also provides ideal principles that influence various aspects of human life. This research aims to identify the elements of idealism contained in the verses of the Koran and how these principles are applied in building a sakinah family. This research uses a qualitative approach. The main source used is the Al-Quran text, while references from various literature, such as books, journals, websites are used as secondary sources to provide additional context and interpretation related to the implementation of Al-Quran values ​​in building a sakinah family. Research findings show that the Al-Qur'an as a guide in forming a sakinah family is an indisputable necessity. The Koran is not only a source of religious teachings, but also provides practical guidance in managing family relationships. Implementation of the values ​​of the Koran, such as love, understanding, patience and good communication, is a solid foundation for the success of creating a harmonious and peaceful family. The existence of the Koran as a guide ensures that every step taken by family members is based on the principles taught by the religion.